Algorithm for automatic fatigue crack growth simulation on welded high strength steels - R. Baptista; J. Marques; V. Infante (Fracture and Structural Integrity)
Nowadays the demand for high strength steels is increasing. In order to design and develop high performance products, it is essential to understand the fatigue behavior of these materials. When considering welded components, the fatigue behavior is even more complex. The material parameters may change along the crack growth and mixed mode crack propagation may also occur. To assess welded high strength steel fatigue behavior, different welded CT specimens were tested. The Paris law material constants were obtained for the heat affected zone material. Fatigue crack growth life predictions were made using the obtained parameters and different automatic techniques. Previous work showed that the ABAQUS extended finite element method can predict fatigue crack growth, but as the implementation of the Paris law is not straight forward, to many conversions must be made and the results are too computer intensive. A simpler and more intuitive Python algorithm was developed, to enable the use of the experimental material parameters, to predict the crack propagation path. The obtain results show a good agreement with both the experimental Paris curves, and the analytical solution.